2016
DOI: 10.1016/j.neulet.2016.04.033
|View full text |Cite
|
Sign up to set email alerts
|

Confounding effect of EEG implantation surgery: Inadequacy of surgical control in a two hit model of temporal lobe epilepsy

Abstract: In rodent models of epilepsy, EEG implantation surgery is an essential modality to evaluate electrographic seizures. The inflammatory consequences of EEG electrode-implantation and their resultant effects on seizure susceptibility are unclear. We evaluated electrode-implantation in a two-hit model of epileptogenesis in C57BL/6 mice that included brief, recurrent febrile seizures (FS) at P14 and kainic acid induced seizures (KA-SZ) at P28. During KA-SZ, latencies to first electrographic and behavioral seizures,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 20 publications
0
11
0
Order By: Relevance
“…One study employing a kainic acid seizure paradigm found that EEG implantation increased seizure endpoints (specifically mortality) regardless of experimental groups. 28 This paper has two key differences from our study, however: (1) they use juvenile mice, and (2) their postoperative recovery period is much shorter (3 days). They suggest that increased seizure susceptibility is due to inflammation, which may or may not resolve at a later time point.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…One study employing a kainic acid seizure paradigm found that EEG implantation increased seizure endpoints (specifically mortality) regardless of experimental groups. 28 This paper has two key differences from our study, however: (1) they use juvenile mice, and (2) their postoperative recovery period is much shorter (3 days). They suggest that increased seizure susceptibility is due to inflammation, which may or may not resolve at a later time point.…”
Section: Discussionmentioning
confidence: 77%
“… 27 EEG implantation increased seizures in the acute setting in a kainic acid seizure paradigm. 28 Furthermore, it is unclear if prior studies considered these factors in their preclinical research.…”
Section: Introductionmentioning
confidence: 99%
“…One study reported that EEG electrode implantation increased seizure susceptibility in mice. Furthermore, EEG implanted mice exhibited significantly more microglial activation after experiencing seizures than did their sham-operated controls (Balzekas et al, 2016). We suggest that immunohistochemical analysis of the brain should always be conducted after such experiments to exclude animals exhibiting significant inflammation or tissue damage of the brain or dura.…”
Section: Discussionmentioning
confidence: 91%
“…Combining long term home-cage monitoring with synchronized high-quality wireless EEG remains an important ongoing objective but may reveal observer effects across both ictal and interictal measures: the mere placement of EEG electrodes in mice (tethered or wireless) may impair mobility, sleep and neurovegetative function through pain or direct physical hindrance. Further, EEG implantation surgery may itself increase seizure threshold through pain, impaired sleep and postoperative inflammation [68], as well as through unintended cortical microlesions that may occur when electrodes are inadvertently advanced to subdural depths [69].…”
Section: Discussionmentioning
confidence: 99%